Dampak kearifan lokal tradisi sedekah laut bagi masyarakat tambak lorok kota semarang - Roisyah Budiati; Raudya Setya Wismoko Putri; Mochamad Ainul Yaqin; Umar Yampap; Yonarlianto Tembang (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
The implementation of the Sea Alms in Tambak Lorok Village is carried out in the months of Apit and Suro, this year the sea alms will be held in June. This study aims to examine the process of sea alms and analyze the impact of the sea alms ceremony. The method used is descriptive with a qualitative approach. Data collection in this study through observation, questionnaires, interviews, and documents. The location of this research is Tambak Lorok Village, Tanjungmas Village. Sea alms have cultural values ​​​​of mutual cooperation, sharing by feeding marine biota, there are disaster values, and there are cultural values ​​​​of loving the surrounding nature. The positive impacts of sea alms are as an effort to preserve fish and marine biota, as an effort to reduce plastic waste, strengthen brotherhood, and create economic impacts in the form of increased income due to boat rentals at the sea alms ceremony. The negative impacts of sea alms include throwing women's clothing items that are very difficult to decompose, so they can become trash on the seabed and can damage coral reefs. Makeup items such as vanity mirrors that are thrown into the sea are also very dangerous for marine life, as glass is a sharp object and can injure marine life. Glass embedded in the seabed can also be dangerous for divers.